Assessing the effect of semen parameters on pregnancy outcome in couples undergoing intrauterine insemination for unexplained infertility and male infertility (Annals of Medical Research, 2025)
Aim: The aim is to investigate the effect of semen parameters in predicting pregnancy outcomes in the unexplained infertility and male infertility groups among couples who received insemination within the scope of infertility treatment.Materials and Methods: In our study, spermiogram data were retrospectively obtained from 57 couples diagnosed with male infertility and 251 couples diagnosed with unexplained infertility who applied to Gaziantep Cengiz Gökçek Obstetrics and Gynecology Hospital ART Clinic and underwent IUI between July 2021 and July 2023, and the demographic data of the patients were analyzed. Before IUI, ovulation induction with an aromatase inhibitor and recombinant FSH was performed in female patients. Semen was collected from the male patient on the day of the procedure, and semen analysis was performed. Semen prepared by applying the semen preparation protocol was injected into the uterus with an insemination catheter. Pregnancy in the patients was assessed by serum beta-hCG on day 14 after the procedure.Results: The positive pregnancy rate for male infertility was 10.5%, and the positive pregnancy rate for unexplained infertility was 13.5%. There was no association between unexplained infertility and spermiogram parameters. In male infertility, there was a relation between Total Progressive Motile Sperm (TPMS) density and post-wash TPMS Count (TPMSC) and positivity of pregnancy (p=0.035, p=0.017, respectively).Conclusion: Semen parameters generally don't predict pregnancy outcomes in couples with unexplained infertility. However, for couples seeking help for male infertility, calculating Total Progressive Motile Sperm (TPMS) density and post-wash TPMS Count (TPMSC) during the initial semen evaluation is a crucial step in predicting pregnancy outcomes.
Keywords: Male infertility; Unexplained infertility; Spermiogram; Intrauterine insemination